Spatial manipulating spin-polarization and tunneling patterns in graphene spirals via periphery structural modification. (March 2017) - Xu, Xiaodong; Tian, Ruihuan; Wang, Qiang; Li, Weiqi; Jiang, Yongyuan; Zhou, Xin; Zhang, Guiling; Liu, Linhua; Tian, Wei Quan
Abstract: A new carbon-based morphology, graphene spirals (GSs), possesses interesting electronic features with inter-layer interaction and intra-layer interaction, ascribed to its unique intra-system electronic coupling states. The spin-polarization and the tunneling patterns of GSs manipulated by the periphery structural modification were investigated in detail with first principle calculations. The spin-polarized edge-states and transport properties can be enhanced and modulated by the constructed trigonal corners efficiently. Governed by the position and the number of the introduced carbon-hexagons, diverse spin-polarized tunneling states and various edge-state couplings between central spiral structure and electrodes can be achieved. More significantly, the contribution of inter-layer tunneling and intra-layer tunneling can be dominated by the topological signatures of GSs. For all spiral conformations, inter-layer tunneling always contributes to the net spin-dependent current. Remarkably, when carbon-hexagons are introduced at some typical positions, the complete spiral current along spiral construction is induced by intra-layer tunneling. Those features provide a good tunability of spin-polarized couplings and tunneling patterns in GSs for spintronic applications. Graphical abstract: